Hydrothermal Fabrication of Three‐Dimensional Secondary Battery Anodes. (5th September 2014) - Liu, Jinyun; Zhang, Hui Gang; Wang, Junjie; Cho, Jiung; Pikul, James H.; Epstein, Eric S.; Huang, Xingjiu; Liu, Jinhuai; King, William P.; Braun, Paul V.
<x xml:space="preserve">Abstract</x> A generalized hydrothermal strategy for fabricating three‐dimensional (3D) battery electrodes is presented. The hydrothermal growth deposits electrochemically active nanomaterials uniformly throughout the complex 3D mesostructure of the scaffold. Ni inverse opals coated with SnO2 nanoparticles or Co3O4 nanoplatelets, and SiO2 inverse opals coated with Fe3O4 are fabricated, all of which show attractive properties including good capacity retention and C‐rate performances. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>